Wallpaper - Blackley, Lachlan (London : Laurence King, 2006)
The revival of ornament has seen a resurgence of interest in wallpaper design. This text showcases fresh wallpaper designs from 50 artists, including graphic designers such as Kam Tang, fashion designers such as Eley Kishimoto & illustrators such as Chisato Shinya, as well as new directions from established wallpaper designers.
Keywords: Wallpaper; Wallpaper -- Design; House and Home